Generator Jadwal Mengajar Dosen Dengan Perkecualian Memakai Teori Himpunan - Katon Wijana; Harianto Kristanto; Yetli Oslan (Jurnal Terapan Teknologi Informasi, 2022)
Lecturers have the task of "tri darma perguruan tinggi", namely teaching, dedication and research, therefore lecturers' activities are not solely teaching in class but also carry out other activities related to this matter. In this case the head of the department, as a compiler of the class schedule, only knows the course schedules that are taught by the lecturer concerned and does not know other activities carried out by the lecturer. In this case the author wants to use set theory to create a schedule generator that can exclude certain schedule lecturers on certain schedules. The set theory can classify which parts are subsets or non-subsets, can also identify intersection of several sets and can combine one set with another set. The activity schedule basically can be categorized as a set that can be operated using these theories, so it is possible to identify which schedules are colliding (intersecting) and which schedules are still available (not the subsets) for certain lecturers. By implementing set theory on the lecturer teaching schedule database plus the exceptions, it is expected that the lecturer teaching schedule will be obtained in accordance with the teaching schedule and the schedule of each lecturer's activities